2 ^ (2x-3) 3 * 2 ^ (x-2) + 1 = 0

2 ^ (2x-3) 3 * 2 ^ (x-2) + 1 = 0

  •  \ displaystyle 2 ^ {2x-3} -3 * 2 ^ {x- 2} + 1 = 0 \\ \\ \ frac {2 ^ {2x}} {8} - \ frac {3 * 2 ^ {x}} {4} + 1 = 0 \\ \\ \ frac {2 ^ {2x} -6 * 2 ^ {x} +8} {8} = 0 \\ \\ 2 ^ {2x} -6 * 2 ^ {x} + 8 = 0 \\ 2 ^ {x} = y \ \ y ^ {2} -6y + 8 = 0 \\ D = b ^ {2} -4ac = 36-32 = 4 \\ \\ y_ {1,2} = \ frac {-bб \ sqrt {D} } {2a} \\ \\ y_ {1} = 4 \\ y_ {2} = 2 \\ \\ 2 ^ {x} = 4 \\ x = 2 \\ \\ 2 ^ {x} = 2 \ \ x = 1

    Відповідь: {1; 2}

You may also like

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *

52 − 47 =